PENINGKATAN KESADARAN LINGKUNGAN DAN PARTISIPASI MASYARAKAT MELALUI SOSIALISASI KONDISI TERKINI EKOSISTEM PERAIRAN DI KELURAHAN SENGGARANG, KOTA TANJUNGPINANG - Sabriyati, Deni; Apriadi, Tri; Melani, Winny Retna; Zulfikar, Andi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
Coastal and small island ecosystems play a central role in the development and well-being of communities. In Senggarang Subdistrict, Tanjungpinang City, the condition of coastal ecosystems is a crucial focus for maintaining balance and productivity. Through community engagement activities, this initiative aims to enhance environmental awareness and knowledge among residents regarding the monitoring of the current conditions of the aquatic ecosystem in the area. The partners in this endeavor are the residents of Senggarang Subdistrict, living in proximity to the aquatic environment. The methods employed include Mapping waters condition, socialization (commencing with pre-tests and concluding with post-tests), dissemination of information through an e-catalog, and focus group discussions (FGDs). The outcomes of this initiative are mapping the potential of coastal and aquatic ecosystems, creating an e-catalog containing up-to-date information on water conditions, upgrading of community knowledge about it and identifying issues faced by the community. Through active communication with the community, challenges such as coastal cleanliness and flood disasters have been identified, requiring special attention. The significance of these engagement outcomes lies in the effort to enhance community awareness and knowledge of their environment for further actions in sustaining and managing aquatic ecosystems effectively. References Ginting, R.J., Apriadi, T. & Zulfikar, A. (2023). Kepadatan Perifiton Epifitik dan Kaitannya dengan Kualitas Perairan di Perairan Senggarang Besar Kota Tanjungpinang Kepulauan Riau. Skripsi. UMRAH. Hanifah, P. N., Nugraha, A.H. & Zulfikar, A. (2023). Laju Pertumbuhan dan Produksi Biomassa Daun Lamun di Perairan Senggarang Besar, Kota Tanjungpinang Kepulauan Riau.. Melani, W. R., Apriadi, T., Muzammil, W., Zulfikar, A., & Sabriyati, D. (2021). Penjaringan Isu Startegis Permasalahan Pengelolaan Waduk Sumber Air Baku di Pulau Bintan. Urnal Panrita Abdi, 5(3), 365–372. http://journal.unhas.ac.id/index.php/panritaabdi. Melani, W. R., Zulfikar, A., Apriadi, T., Muzammil, W., & Sabriyati, D. (2022). Characterization of hydrological aspects in Kolong Enam Retention Basin, Kijang, Bintan Island, Indonesia. In E3S Web of Conferences (Vol. 339, p. 02010). EDP Sciences. https://doi.org/10.1051/e3sconf/202233902010. Muftadi, A., Melani, W. R. & Zulfikar, A. (2023). Tingkat Kesuburan Perairan di Senggarang Besar, Kota Tanjungpinang Kepulauan Riau. Skripsi. UMRAH. Murray, N.J., Bunting, P., Canto, R.F., Hilarides, L., Kennedy, E.V., Lucas, R.M., Lyons, M.B., Navarro, A., Roelfsema, C.M., Rosenqvist, A., 2022. coastTrain: A Global Reference Library for Coastal Ecosystems. Remote Sens. 14, 5766. https://doi.org/10.3390/rs14225766. Muzammil, W., Apriadi, T., Melani, W. R., Oktavia, Y., Zahra, A., Ma'mun, A. & Zulfikar, A. (2022). Pengenalan Biota Laut Dilindungi melalui e-Book “Dugong & Friends” dalam Meningkatkan Kesadaran Masyarakat terhadap Kelestarian Sumber Daya Perikanan. Jurnal Pengabdian Kepada Masyarakat Maritim, 5(1), 11-19. Muzammil, W., Apriadi, T., Melani, W. R., Zulfikar, A.(2021). Pengenalan Biota Akuatik Aliran Sungai Senggarang dengan E-Katalog melalui pembelajaran tatap muka sesuai protokol kesehatan Covid-19. Seminar Nasional Pemberdayaan Masyarakat, 2021–2032. https://doi.org/10.31258/unricsce.3.324-332. Nevertari, S. P. & Arumsari, R. Y., 2017. Perancangan Video Sosialisasi Taman-taman Tematik di Kota Bandung. E-proceeding of art & design. Vol 4(3) 547. Nurjannah, M., & Irawan, H. (2013). Keanekaragaman Gastropoda Di Padang Lamun Perairan Kelurahan Senggarang Kota Tanjungpinang Provinsi Kepulauan Riau. Repository UMRAH. Putra, R.A., Melani, R.M., & Suryanti, A. (2020). Makrozoobentos sebagai Bioindikator Kualitas Perairan di Senggarang Besar Kota Tanjungpinang. Jurnal Akuatiklestari, 4(1): 20-27. DOI: https://doi.org/10.31629/akuatiklestari.v4i1.2486. Rasip, A., Apriadi, T. & Azizah, D. (2023). Kelimpahan Zooplankton Berdasarkan Waktu dan Kedalaman di Perairan Senggarang Besar Tanjungpinang. Skripsi. UMRAH. Sinaga, M.V., Melani, W. R. & Zulfikar, A. (2023). Sampah Laut dan Kaitannya dengan Kepadatan Gastropoda di Perairan Senggarang Besar Kota Tanjungpinang. Skripsi. UMRAH. Skripsi. UMRAH. Undang-undang No 2 tahun 2007 tentang Pengelolaan Wilayah Pesisir Dan Pulau-Pulau Kecil. Yanti, E., Apriadi, T. & Zulfikar, A. (2023). Keanekaragaman Fitoplankton dan Kaitannya dengan Kondisi Perairan di Senggarang Besar Kota Tanjungpinang Kepulauan Riau. Skripsi. UMRAH